Persistent organic pollutants (PCBs and OCP) in air and soil from Ulaanbaatar and the Lake Hovsgol region, Mongolia - Mamontova, EA; Tarasova, EN; Ganchimeg, D; Kuzmin, MI; Mamontov, AA; Khomutova, M Yu; Burmaa, G; Odontuya, G; Erdenebayasgalan, G (Mongolian journal of chemistry, 2014)
The investigations of POPs in soil and air in three urban and rural sites of the Mongolia are presented. The POPs distribution in air repeats the POPs distribution in soil on the area investigated. The POPs levels in soil and air are lower than maximum permissible concentrations (MPC) and preliminary permissible concentrations (PPC) of PCBs and OCP accepted in Russia. POPs levels in Mongolian soil obtained in the investigation are comparable with those from background areas of the world. POPs levels in Mongolian air are in the frame of concentrations found in the world. The PCB homological pattern in soil near electric power station in Ulaanbaatar is close to homological pattern in PCB technical mixture (Sovol or Arochlor 1254). The homological patterns in soil from other sites changed due to the redistribution of PCB congeners in the environment. The ratio of DDT and its metabolites indicates fresh entrance of DDT in the environment of Mongolia due to the atmospheric transboundary transport from countries using DDT (China, India) or from local agricultural sources. Hazard indexes in result from human exposure with POPs in soil and air are lower by 2-4 orders than 1 that denotes the possible default of disturbances in target organ and system. CR under the same scenario corresponds to the first diapason that is taken by population as negligible risk, not differ from usual everyday risks. Such risks don’t require additional measures for the reducing of risks and their levels are a subject of periodical control. The necessity of additional investigation of POPs distribution and the fate in Mongolian environment is indicated.DOI: http://dx.doi.org/10.5564/mjc.v12i0.176 Mongolian Journal of Chemistry Vol.12 2011: 69-77